Tree-rings reflect the impact of climate change on Quercus ilex L. along a temperature gradient in Spain over the last 100years - Gea-Izquierdo, G.; Cherubini, P.; Cañellas, I. (Forest Ecology and Management, 2011)
We analyzed tree rings over the past 100 years to understand the response of Quercus ilex L. to climate change at four different sites along a temperature gradient in a highly anthropogenically transformed ecosystem. To test the hypothesis of a climate change related decrease in productivity at warmer sites, we discuss the effect of historical management on the growth of forest stands and the spatio-temporal variability of growth in response to climate, analyzing departures from linearity in that relationship. We reconstructed stand history and investigated past growth trends using tree-rings. Then we used a dendroecological approach to study the regional, local and age-dependent response to climate, analyzing the relationship between precipitation and tree growth using non-linear mixed models. Tree rings reﬂected the origin of the studied landscape, mainly a simpliﬁcation of an original closed forest and progressive canopy opening for agrosilvopastoral purposes after the mid 1800s. As expected, trees were principally responding to water availability, and regional growth (as expressed by the ﬁrst principal component from the matrix of chronologies) was highly responsive to hydrological year precipitation (r = 0.7). In this water limited ecosystem, the response of growth to precipitation was asymptotic and independent of age, but variable in time. Maximum growth was variable at the different sites and the non-linear function of growth saturated (i.e. reached an asymptote) at temperature dependent site speciﬁc precipitation levels within the range considered in the region to lead a shift towards deciduous species dominated woodlands (around 600 mm, variable with mean temperature). Only trees at warmer sites showed symptoms of growth decline, most likely explained by water stress increase in the last decades affecting the highly transformed open (i.e. low competition) tree structure. Stands at colder locations did not show any negative growth trend and may beneﬁt from the current increase in winter temperatures. Coinciding with the decrease in productivity, trees at warmer sites responded more to moisture availability, exhibited a slower response to precipitation and reached maximum growth at higher precipitation levels than trees at colder sites. This suggests that warmer stands are threatened by climate change. The non-linear response of growth to precipitation described is meaningful for different ecological applications and provides new insights in the way trees respond to climate.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: competition; Dendroecology; Drought; Non-linear response; water stress

Analysis of holm oak intraspecific competition using Gamma regression - Gea-Izquierdo, G.; Cañellas, I. (Forest Science, 2009)
Analysis of plant competition is a major issue in ecology and forestry, as it influences plant growth and plant-environment interactions. Competition is expected to be lower in the sparse tree stratum of open woodlands and agroforestry systems than in closed forests. We have analyzed competition in open woodlands of Quercus ilex in the Iberian Peninsula by studying a 10-year diameter growth increment from collected samples and from consecutive National Forest Inventories. Density was the competition index selected in all models, outperforming more complex distance-dependent indices. The models showed that competition is playing a role in growth but that the covariate most correlated with growth is age or dbh as a surrogate of age. Therefore, below-ground competition is likely to be limiting tree growth, but below-ground competition is lower in open woodlands compared with that in denser forests and thus potential growth (which is strongly linked to age) is almost expressed. Model behavior was improved when data were fitted directly using generalized linear models, which do not require transforming of the dependent variable. Our results showed that modeling growth with the gamma probability distribution resulted in better models compared with Gaussian linear models. Gamma regression offers a great potential for many forestry applications.
Keywords: Dehesa; diameter increment growth; generalized linear model; Quercus ilex

Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G.; Montero, G.; Cañellas, I. (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G.; Cañellas, I.; Montero, G. (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Silviculture and Carbon Sequestration in Mediterranean Oak Forests - Cañellas, I.; Sánchez-González, M.; Bogino, S. M.; Adame, P.; Herrero, C.; ROIG, S.; Paulo, J. A.; Bravo, F. (Managing Forest Ecosystems: The Challenge of Climate Change, 2008)
The Kyoto Protocol requires every industrialized country to have a transparent and verifiable method for estimating the size and evolution of the carbon stored in forest ecosystems. The intergovernmental panel on climate change (IPCC, 2007) predicts the evolution of the stock over the first commitment period (2008–2012) using the “bottom-up approach”. This approach is based on the use of data from national or regional forest inventories. The biomass of living trees including their dead parts comprises the main carbon pool in forest ecosystems along with the biomass of understorey plants, litter, woody debris and soil organic matter (Pignard et al., 2004). The objective of this chapter is to present some of the studies currently being carried out in Spain and Portugal which are concerned with the possibility of estimating the amount of carbon fixed by two of the main oak species in the Iberian Peninsula; rebollo oak (Quercus pyrenaica Willd.) and cork oak (Quercus suber L.). Three different methodological approaches have been used. The first approach is to use growth models to evaluate the carbon sequestration in both cork and wood over the life of a cork oak plantation. This approach has been applied both for Spain and Portugal. The second approach involves using a yield table as a tool to estimate the carbon sequestration in Quercus pyrenaica forests based on Spanish National Forest Inventories. In a third approach, data from a network of plots is used to estimate the carbon sequestration in pure and mixed Quercus pyrenaica forests. The application of these different methodologies would allow us to forecast and improve the carbon sequestration in oak forests as well as increasing our understanding of their dynamics.
The following values have no corresponding Zotero field: periodical: Managing Forest Ecosystems: The Challenge of Climate Change, electronic-resource-num: 10.1007/978-1-4020-8343-3
Keywords: biomass; carbon stock; Kyoto protocol; Portugal; Spain

Generalized height-diameter and crown diameter prediction models for cork oak forests in Spain - Sánchez-González, M.; Cañellas, I.; Montero, G. (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
A generalized height-diameter equation, along with a crown diameter prediction equation for cork oak forests in Spain were developed based on data from the Second Spanish Forest Inventory. Nine generalised height-diameter equations were selected as candidate functions to model the height-diameter under cork relationship, while for the crown diameter prediction model five linear and non-linear equations were tested. The equations were fitted using the mixedeffects model approach. The Stoffels & Van Soest power equation, constrained to pass through the point of dominant diameter and dominant height, was selected as the generalised height-diameter model. Regarding the crown diameter prediction model, the parable function without the intercept and with quadratic mean diameter incorporated as a fixed effect into the b parameter, proved to be the model with best prediction capabilities. The models were validated by characterising the model error using the PRESS (Prediction Sum of Squares) statistic. Both equations will be submodels of the ALCORNOQUE v1.0, a management oriented growth and yield model for cork oak forests in Spain.
Keywords: crown width; forest growth modelling; height-diameter relationship; mixed effects models; Quercus suber

Influencia del tamaño de bellota y del régimen de riego en la calidad de planta de alcornoque cultivada en vivero - Pardos Mínguez, M.; Cañellas, I.; Bachiller, A. (II Congreso Forestal Español, 1997)
The effect of three acorn sizes (small, medium and large, 2.5, 5 and 8.8 g mean fresh weight, respectively) and two irrigation regimes (Rl=2R2) in the growth of cork oak containerized (Forest Pot 300) seedlings was studied. The seedlings were grown in the nursery for one year.The results showed the influence of the acorn size on caliper, root volume, shoot, root and acorn dry weights, leaf area, leaf weight ratio (L WR), leaf area ratio (LAR), midday water potential and transpiration. Irrigation was statistically significant for height and totalleaf area. Water potential reached less than -2 MPa in July. This fact reveals the adaptation of the species to drought.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español
Keywords: acorn size; irrigation; Quercus suber; seedling quality